Basidiomycetes in selected mangove areas in Guimaras and Iloilo, Philippines. - Pineda, Peachy Mae A (2011.)
Basidiomycetes play important roles in the ecosystem: some of them are considered saprophytic, pathogens and symbionts. These organisms can be also useful since they are mainly involved in the recycling of nature. They have enzymes capable of degrading wood, but little is known about their diversity and ecology in the mangrove ecosytem. The samples were collected from Getulio and Luzaran in Guimaras and Tabucan (Mandurriao, Nabitasan (Leganes) and Ermita (Dumangas) in Iloilo from August to Dec. 2010. A total of eleven genera were identified from sixty eight wood samples. These include Aurecularia, Calathella, Crepidotus, Ganoderma, Halocyphina, Inonotus, Peniophora, Pcynoporus, Schizophyllum, Trametes and Tremella. In Getulio and Bagatnan, the most frequent collected species was Schizophyllum while in Taklong, Dumangas and Leganes, the most frequent species was Ganoderma and in Mandurriao, Calathella and Halocyphina have equal frequency of occurrence. The genera that occurred very frequent were Ganoderma (26.5 percent) and Schizophyllum (19.1 percent). The frequent genera were Calathella (5.8 percent), Halocyphina (7.4 percent), Inonotus (5.9 percent), Peniophora (7.4 percent) and Pycoporus (7.4 percent). Genera Auricularia (4.41 percent), Crepidotus (1.5 percent), Tremella (1.5 percent) and six unknowns belong to infrequent species. The site that had the most number of species and had the highest frequency of occurrence basidiomycetes was in Bagatnan, Guimaras. This preliminary study had shown that mangroves harbor numerous species of Basidomycetes indicating a high diversity on this fragile ecosytem. Thus, more studies are needed to document on their occurrence and study further their role in nutrient dynamics in a mangrove habitat as well as their potential application in biotechnology.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangrove -- Guimaras; Mangrove -- Iloilo, Philippines